Flat layout affecting social interaction / Ahmad Waldan Badli Hisham and Neta Suredah Baharum - Badli Hisham, Ahmad Waldan; Baharum, Neta Suredah (2018)
Living cost influences lifestyle. Shelter is regarded as a necessity in living. This has brought about the demand for low cost flats resulting in the rising number of such flats. Population living in this lifestyle bear the deficiency of basic accommodation and proper maintenance, due to unregulated inspection within their compound. Social integration within the population has become a key point in helping create a better society. From the layout design of the building until the facility is ready, every aspect must be taken care of, thus it will help in building a society space that spill into outdoors. This paper explores the social interaction between users in different kinds of flat layout. It is through this comparative study, the concept of how different flats' configuration affects the different pattern of social behavior can be investigated.